1994
DOI: 10.1038/372150a0
|View full text |Cite|
|
Sign up to set email alerts
|

Oligosaccharide ligands for NKR-P1 protein activate NK cells and cytotoxicity

Abstract: A diversity of high-affinity oligosaccharide ligands are identified for NKR-P1, a membrane protein on natural killer (NK) cells which contains an extracellular Ca(2+)-dependent lectin domain. Interactions of such oligosaccharides on the target cell surface with NKR-P1 on the killer cell surface are crucial both for target cell recognition and for delivery of stimulatory or inhibitory signals linked to the NK cytolytic machinery. NK-resistant tumour cells are rendered susceptible by preincubation with liposomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
133
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 248 publications
(137 citation statements)
references
References 45 publications
3
133
1
Order By: Relevance
“…This is a recombinant protein prepared by bacterial expression of the extracellular portion of rat NKR-P1A antigen starting with leucine 66 [8]. It has been shown to be a carbohydrate binding protein (animal lectin [9]) that binds N-acetyl-D-glucosamine in its free or conjugated form [8,10,11] in addition to the spectrum of carbohydrates bearing acidic functionalities [12]. We have found that in plate inhibition experiments the low molecular mass GlcNAc-terminated glycoclusters are good ligands for sNKR-P1A with inhibition activities comparable with the classical high a¤nity neoglycoprotein ligands.…”
Section: Introductionmentioning
confidence: 99%
“…This is a recombinant protein prepared by bacterial expression of the extracellular portion of rat NKR-P1A antigen starting with leucine 66 [8]. It has been shown to be a carbohydrate binding protein (animal lectin [9]) that binds N-acetyl-D-glucosamine in its free or conjugated form [8,10,11] in addition to the spectrum of carbohydrates bearing acidic functionalities [12]. We have found that in plate inhibition experiments the low molecular mass GlcNAc-terminated glycoclusters are good ligands for sNKR-P1A with inhibition activities comparable with the classical high a¤nity neoglycoprotein ligands.…”
Section: Introductionmentioning
confidence: 99%
“…In support of this, we have previously shown that invariant Vα24+NKT-cells exhibit cytolytic antitumour activities against some tumour cell lines that do not express CD1d through killing mechanisms that are distinct from both those of NK-cells and T-cells (Nicol et al, 1999). Also, the presence of NKR-P1A receptors, which may be linked to the cytolytic activity, argues for an important cytotoxic function of human invariant Vα24+NKT-cells other than that exerted through TCR-mediated recognition of CD1d (Azzoni et al, 1998;Bezouska et al, 1994). Alternatively, the anti-tumour effects could be exerted through inhibition of proliferation, either by direct …”
mentioning
confidence: 99%
“…Among other NKRP1 family members, NKRP1A (with high sequence identity to NKRP1D and others in the NKRP1 family in the extracellular domain) has been reported to bind various sugars, including sulfated fucose-containing Le x and Le a oligosaccharides as well the HMW and LMW sugars that OCIL recognizes (8). The significance of OCIL recognition of similar sulfated sugars is unclear, but suggests that sugar recognition may play a role in the interaction of each of these molecules to enable NK cell mediated cytotoxicity, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Lectins are nonenzymatic sugar-binding proteins that bind specific carbohydrate moieties on cell surfaces, the extracellular matrix, and secreted glycoproteins, and such C-type lectin carbohydrate binding can play an important role in cellular functions (7,8). Alignment of the protein sequences of murine OCIL with human CD69 and rat mannose-binding protein A is shown in Fig.…”
mentioning
confidence: 99%